ChemInform Abstract: 2‐Trifluoromethylthiolation of Glycals. Issue 46 (October 2016) - Yu, Yang; Xiong, De‐Cai; Ye, Xin‐Shan
Abstract: Application of the title reaction to the 2‐trifluoromethylthiolation of lactals and deprotection of the products is demonstrated.